The impact of the entry of national retailers into townships on South African spaza shops in Bloemfontein - Masisi, Gosiame Moanaco (University of the Free State, 2020)
Purpose: The primary objective of this research was to investigate the impact of the entry of national retailers into the Bochabela, Bloemanda, Freedom Square, Grassland, Heidedal, Joe Slovo, Namibia Phahameng, and Rocklands locations on South African-owned spaza shops in Bloemfontein. Methodology: The research methodology was positivist in nature and used a quantitative method design with a survey research strategy using a 5-point Likert scale questionnaire. A simple random sampling strategy was used, and the study respondents comprised 104 spaza shop owners. The online questionnaire was distributed to all respondents using the online questionnaire. Findings: The main results confirm that spaza shops near shopping malls are more likely to be negatively impacted than those in outlying areas. In a competitive market, spaza shops are vulnerable to prices. Very few of the spaza shops have adopted business strategies in response to their larger competitor. Conclusion: Local spaza shop owners therefore need to implement measurable competitive strategies to improve competitiveness in the retail industry.
Dissertation (MBA (Business Administration))--University of the Free State, 2020
Keywords: national retailers; spaza shop; sustainable competitive advantage; competition strategies; small business; shopping mall